Target Receptors in the Control of Insect Pests. - Cohen, Ephraim (Advances in insect physiology, 2014)
This volume of Advances in Insect Physiology contains comprehensive interdisciplinary reviews on basic and practical aspects relevant to major target receptors for crucial physiological functions and mechanisms in prokaryotic and eukaryotic organisms, particularly insects. Chapters emphasize advanced genomic, molecular biology, chemical, and proteomic research on the receptors and their corresponding agonist and antagonist ligands. The book encompasses target systems such as sodium channels, octopamine/tyramine receptors, ABC transporters, acetylcholinesterase as a target enzyme, juveni.